2019
DOI: 10.1175/jcli-d-19-0042.1
|View full text |Cite
|
Sign up to set email alerts
|

The Zonal Dipole Pattern of Tropical Cyclone Genesis in the Indian Ocean Influenced by the Tropical Indo-Pacific Ocean Sea Surface Temperature Anomalies

Abstract: From a basinwide perspective, the dominant mode of Indian Ocean tropical cyclone genesis (TCG) in September–November (SON) shows an equatorially symmetric east–west zonal dipole pattern, which can explain approximately 13% of the SON TCG variance. This zonal dipole TCG pattern is significantly related to the tripole pattern of the sea surface temperature anomalies (SSTAs) in the tropical Indo-Pacific Ocean (IPT). The IPT, which is a combined interbasin mode and presents a dipole pattern of SSTAs in the tropica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 41 publications
(75 reference statements)
1
19
0
Order By: Relevance
“…In contrast, an obvious descending branch of the Walker circulation appears in the AS, which inhibits water transport in the upward direction and is unfavorable for TCG. The related processes have been reported in previous studies [12,24].…”
Section: Quantitative Analysis Of the Environmental Factors For Gpisupporting
confidence: 72%
See 3 more Smart Citations
“…In contrast, an obvious descending branch of the Walker circulation appears in the AS, which inhibits water transport in the upward direction and is unfavorable for TCG. The related processes have been reported in previous studies [12,24].…”
Section: Quantitative Analysis Of the Environmental Factors For Gpisupporting
confidence: 72%
“…resulting in different contributions from humidity [24]. Based on this comprehensive analysis of the change in GPI, the BOB has conditions that are more favorable to TCG.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have also shown that SST affects the distribution of environmental factors through the Walker circulation [48,49]. In addition to the SST anomaly in the Pacific, the SST anomaly in the Indian Ocean can also affect TC frequency over the WNP basin by means of modulating the monsoon circulation and the equatorial Kelvin wave activity [50][51][52]. Thus, the extremely high TC frequency in November 2019 may be associated with the atmospheric circulation in response to the tropics-wide SST change.…”
Section: The Role Of Regional Sst Changes In Promoting Tc Genesis In ...mentioning
confidence: 99%